Penentuan Jalur Potensial BRT yang Menghubungkan Pusat-Pusat Kegiatan di Kota Makassar Berbasis Indeks Konektivitas - Risky Ayun Amaliyah; Ananto Yudono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
One role of public transportation is to accommodate the community activity. Therefore, the public transportation service must be able to reach distribution of activity center in its service area. However, the existing BRT has not able to serve all the activity center in Makassar yet. This study aims to determine potential route of BRT that connect activity center in Makassar based on their connectivity index. Data used in this study are primary data from observation, while secondary data obtained through previous research. Data obtained then analyzed by overlaying the variables, measuring connectivity index, and descriptive comparative analysis The result of this study show that there are 11 potential rout es that connect the activity centers in Makassar and then divided into 3 classes based on their connectivity index such as first potential, second potential, and third potential routes.